Analysis of Stress Level Prediction Affecting Employee Performance at Limas Dimensi Caraka Company Using the Support Vector Machine Method - Alma Shafira; Oloan Sihombing (Politeknik Negeri Lhokseumawe, 2026)
Work-related stress is the result of actions, situations, and external events that place excessive psychological or physical demands on individuals. Work-related stress indirectly reduces employee performance, leading to a high turnover rate among outsourced employees on a large scale. A problem that almost always arises every year is the demand from outsourced employees for wage increases; this occurs because the cost of living continues to rise every year. The peak of this wage-related issue usually takes the form of strikes carried out by employees against their companies. Regarding the method, there are various algorithms or techniques that can be used for classifying levels of work-related stress, according to previous research and literature. Some previous studies indicate that the SVM (Support Vector Machine) method yields fairly good accuracy. In this study, the results showed no significant anomalies, and no very strong correlations (approaching 1 or -1) were found